2019
DOI: 10.4274/tjps.galenos.2018.20082
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic Acid–Pluronic F127–Palmitic Acid Pentablock Copolymer as a Novel Nanocarrier for Oral Delivery of Glipizide

Abstract: Bu çalışmanın amacı, glipizidin biyoyararlanımı arttırmak ve geleneksel dozaj formunun oral yoldan sık sık verilmesini elimine etmek için nanoteknoloji bazlı oral formülasyonlarını geliştirmektir. Glipizide, biyolojik olarak kısa yarı ömrü ve sınırlı oral biyoyararlanımı olan antidiyabetik bir ilaçtır. Yeni palmitik asit-pluronik F127-palmitik asit (PA-F127) pentablok kopolimer bazlı uzun süreli salım yapan glipizid nanopartikülleri (GNs) in vitro ve in vivo çalışmalar için hazırlanmış ve taranmıştır. Gereç ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The release profile was observed for 24 h and 88.2 ± 2.6 % glipizide was released from GNM1 depicting sustained release. The preliminary burst release of drug from GNM1 may be occurred because of osmotic pressure difference outside and inside the block copolymer ( Kamboj and Verma, 2019 ; Choi. et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The release profile was observed for 24 h and 88.2 ± 2.6 % glipizide was released from GNM1 depicting sustained release. The preliminary burst release of drug from GNM1 may be occurred because of osmotic pressure difference outside and inside the block copolymer ( Kamboj and Verma, 2019 ; Choi. et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of LAF127 copolymer was carried out according to the previously reported methods ( Kamboj and Verma, 2019 ; Bae, et al, 2005 ) . The process involved an esterification reaction between the hydroxyl group of Pluronic F127 and the carboxyl group of lauric acid at the melting phase.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetic evaluation was performed in albino male Wistar rats and comparing the nanoparticles against a GPZ suspension; results showed that the C max of nanoparticles was 2.35times higher than that of the suspension, the t max was of 6 h for nanoparticles and 4 h for the suspension, the t1/2 was 1.5 times higher for nanoparticles than for the suspension, the AUC0  ∞of nanoparticles was 3.3-times higher than that of the suspension, and there was a 1.2times improvement in the mean residence time for nanoparticles. Authors concluded that the oral administration of a dose of nanoparticles equivalent to 1.5 mg/kg of GPZ maintained up to 24 h the therapeutic plasmatic concentrations, suggesting that the issue of administering GPZ two or three times per day can be overcome with the use of nanoparticles 3 .…”
Section: Kamboj and Verma (2019) Developed And Evaluatedmentioning
confidence: 99%
“…Of all DBT reported cases, almost 90% belong to DBT2 2 . Currently, diverse drugs are available for DBT2 treatment; among them is glipizide (GPZ), a drug characterized for having a short elimination half-life (3.4±0.7 h), hence a dosage of two to three tablets per day is needed 3 . The usual initial GPZ dose is of 2.5 to 5 mg per day, but the dose can be increased to reach a maximum effective dose of 10 mg 4 .…”
mentioning
confidence: 99%